Magneto-convection of nanofluid flow over multiple rotating cylinders in a confined space with elastic walls and ventilated ports - Fatih Selimefendigil; Kaouther Ghachem; Hind Albalawi; Badr M. AlShammari; Taher Labidi; Lioua Kolsi (Heliyon, 2024)
In this study, convective heat transfer for nanofluid flow over multiple rotating cylinder in a confined space is analyzed under magnetic field while enclosure has one inlet and one outlet port. Three identical circular cylinder are used and the two walls of the cavity are considered to be elastic. The coupled fluid-structure interaction and magneto-convection problem is solved by finite element method. Impacts of rotational Reynolds number (Rew between -100 and 100), Hartmann number (Ha between 0 and 50), cylinder size (R between 0.001H and 0.11H) and Cauchy number (Ca between 10−8 and 10−3) on the flow and thermal performance features are explored. The flow field and recirculation inside the cavity are significantly affected by the activation of rotation and magnetic field. The vortices are suppressed by increasing the strength of magnetic field and thermal performance is improved. Thermal performance of 56.6% is achieved by activation of magnetic field at the highest strength with rotations of the circular cylinders. When rotations are active, heat transfer rate is reduced while up to 40% reduction is obtained without magnetic field. Cylinder size has the highest impact on the overall thermal performance improvement while up to 132% enhancements are achieved. The contribution of elastic walls on the thermal performance is slight while less than 5% improvements in the average heat transfer is obtained. An optimization study leads to 12.7% higher thermal performance improvements as compared to best case of parametric computational fluid dynamics simulation results while the optimum values of (Rew, Ha, R) is obtained as (-80.66, 50, 0.11H).